Treadmill Exercise Decreases Aβ Deposition and Counteracts Cognitive Decline in APP/PS1 Mice, Possibly via Hippocampal Microglia Modifications - Zhang, Xianliang; He, Qiang; Huang, Tao; Zhao, Na; Liang, Fei; Xu, Bo; Chen, Xianghe; Li, Tuojian; Bi, Jianzhong (Frontiers in Aging Neuroscience, 2019)
Recent studies have suggested that exercise may be beneficial to Alzheimer’s disease. However, the underlying mechanisms were not elucidated. The present study investigated the beneficial effects of treadmill exercise on cognitive function in APP/PS1 mice and its potential mechanisms. Mice underwent 12 weeks of treadmill exercise. The results demonstrated that treadmill exercise preserved hippocampal cognitive function. Treadmill exercise also strongly suppressed Aβ accumulation. Treadmill exercise significantly inhibited neuroinflammation, which was characterized by a remarkably reduced expression of pro-inflammatory factors and increased expression of anti-inflammatory mediators in the hippocampus, which resulted from a shift in activated microglia from the M1 to M2 phenotype. Treadmill exercise strongly attenuated oxidative stress via a marked reduction in methane dicarboxylic aldehyde (MDA) level and dramatically elevated SOD and Mn-SOD activities in the hippocampus. These findings suggest that treadmill exercise prevents the decrease in hippocampal-dependent cognitive function via decreased neuroinflammation, oxidative stress, and Aβ levels.